Elevated Troponin Serum Levels in Adult Onset Still’s Disease - Carlo Umberto Manzini; Lucio Brugioni; Michele Colaci; Maurizio Tognetti; Amelia Spinella; Marco Sebastiani; Dilia Giuggioli; Clodoveo Ferri (Case Reports in Rheumatology)
Adult onset Still’s disease (AOSD) is a rare inflammatory systemic disease that occasionally may affect myocardium. Diagnosis is based on typical AOSD symptoms after the exclusion of well-known infectious, neoplastic, or autoimmune/autoinflammatory disorders. In the case of abrupt, recent onset AOSD, it could be particularly difficult to make the differential diagnosis and in particular to early detect the possible heart involvement. This latter event is suggested by the clinical history of the four patients described here, incidentally observed at our emergency room. All cases were referred because of acute illness (high fever, malaise, polyarthralgias, skin rash, and sore throat), successively classified as AOSD, and they presented abnormally high levels of serum troponin without overt symptoms of cardiac involvement. The timely treatment with steroids (3 cases) or ibuprofen (1 case) leads to the remission of clinicoserological manifestations within few weeks. These observations suggest that early myocardial injury might be underestimated or entirely overlooked in patients with AOSD; routine cardiac assessment including troponin evaluation should be mandatory in all patients with suspected AOSD.